Firm's Value Exploration: The Impact Of Intellectual Capital and Net Working Capital (Jurnal Dinamika Akuntansi, 2020)
Intellectual capital (IC) gains more importance nowadays, and hence, this study investigates the impact of IC and net working capital (NWC) on firms’ values creation. If IC has a greater impact than NWC, it indicates that automotive and components companies in Indonesia have paid attention to IC's contribution to increase company value. This study was conducted on 15 automotive and components companies from 2011 to 2018 as this industry utilises more IC and NWC than any other industries. We used panel data regression analysis with random effect model to test the hypothesis of 92 data, with IC calculated through the MVAIC model, and firm’s value is measured by Tobin’s Q. The results show that IC has no significant effect on firms’ value. Meanwhile, NWC has a significant negative effect on firms’ values creation. These important findings suggest that automotive and components firms should apply strategic management in managing IC and NWC to increase the firm’s value.